Direct and indirect connections between cochlear root neurons and facial motor neurons: Pathways underlying the acoustic pinna reflex in the albino rat - Horta Jr., José de Anchieta C. [UNESP]; López, Dolores E.; Alvarez-Morujo, Antonio Jesús; Bittencourt, Jackson C. (Wiley, 2008)
Cochlear root neurons (CRNs) are involved in the acoustic startle reflex, which is widely used in behavioral models of sensorimotor integration. A short-latency component of this reflex, the auricular reflex, promotes pinna movements in response to unexpected loud sounds. However, the pathway involved in the auricular component of the startle reflex is not well understood. We hypothesized that the auricular reflex is mediated by direct and indirect inputs from CRNs to the motoneurons responsible for pinna movement, which are located in the medial subnucleus of the facial motor nucleus (Mot7). To assess whether there is a direct connection between CRNs and auricular motoneurons in the rat, two neuronal tracers were used in conjunction: biotinylated dextran amine, which was injected into the cochlear nerve root, and Fluoro-Gold, which was injected into the levator auris longus muscle. Under light microscopy, close appositions were observed between axon terminals of CRNs and auricular motoneurons. The presence of direct synaptic contact was confirmed at the ultrastructural level. To confirm the indirect connection, biotinylated dextran amine was injected into the auditory-responsive portion of the caudal pontine reticular nucleus, which receives direct input from CRNs. The results confirm that the caudal pontine reticular nucleus also targets the Mot7 and that its terminals are concentrated in the medial subnucleus. Therefore, it is likely that CRNs innervate auricular motoneurons both directly and indirectly, suggesting that these connections participate in the rapid auricular reflex that accompanies the acoustic startle reflex. © 2008 Wiley-Liss, Inc.
Keywords: Acoustic startle reflex; Auricular muscles; Biotinylated dextran amine; Caudal pontine reticular nucleus; Double tract tracing; Fluoro-gold; amine; fluorogold; tracer; acoustic reflex; animal experiment; animal tissue; biotinylation; cochlear nerve; external ear; facial nerve; female; injection; microscopy; motoneuron; movement (physiology); muscle; nerve ending; nerve root; nonhuman; pons reticular formation; priority journal; rat; structure analysis; synapse; ultrastructure; Animals; Cochlear Nerve; Ear Auricle; Efferent Pathways; Female; Motor Cortex; Motor Neurons; Neurons; Rats; Rats, Wistar; Reflex, Acoustic; Startle Reaction